2002
DOI: 10.1046/j.1365-2990.2002.00419.x
|View full text |Cite
|
Sign up to set email alerts
|

Classifying the medulloblastoma: insights from morphology and molecular genetics

Abstract: Significant advances in the treatment of the medulloblastoma (MB) have been made in the last 30 years, reducing mortality by 2-fold. Further improvements in the cure rate require an increased understanding of the biology of MBs, and this will translate into refinements in their classification. Scrutiny of the cytological variation found among MBs has recently led to the concept of the anaplastic MB, which overlaps the large-cell variant and appears to share its poor prognosis. In contrast, the MB with extensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
156
2
6

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(176 citation statements)
references
References 203 publications
10
156
2
6
Order By: Relevance
“…A hierarchical cluster analysis showed that most medulloblastoma patients with anaplastic histology and disseminated disease were grouped together with patients who died. In line with this finding, anaplastic and metastatic medulloblastomas have been correlated with genetic alterations as 17p loss and oncogene amplifications of MYC and NMYC that are associated with unfavorable survival (15,24).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…A hierarchical cluster analysis showed that most medulloblastoma patients with anaplastic histology and disseminated disease were grouped together with patients who died. In line with this finding, anaplastic and metastatic medulloblastomas have been correlated with genetic alterations as 17p loss and oncogene amplifications of MYC and NMYC that are associated with unfavorable survival (15,24).…”
Section: Discussionmentioning
confidence: 59%
“…Gains of chromosomes 7 or 17q were described in up to 60% of all medulloblastoma samples (5,8,24). Interestingly, none of the genes associated with good prognosis were located on these chromosomal regions.…”
Section: Screening For Molecular Markers In Medulloblastomamentioning
confidence: 99%
See 1 more Smart Citation
“…Despite aggressive therapyconsisting of surgery, radiation, and chemotherapy-lethality and morbidity of patients with embryonal CNS tumors remains high (1)(2)(3). Medulloblastoma is thought to arise from granule cell precursors in the external germinal layer of the developing cerebellum (4).…”
Section: Introductionmentioning
confidence: 99%
“…Current treatment regimes are also associated with long-term neurologic and endocrinologic side effects, and disease course is difficult to predict based on current clinical and pathologic indices. 1,4 Thus, a better understanding of the molecular events underlying the development of these tumours could provide the basis of an improved outlook for these patients, through identification of molecular markers for disease stratification and development of molecularly targeted therapeutic regimens.…”
mentioning
confidence: 99%